2010
DOI: 10.4321/s1886-36552010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence: a review of pharmacy education, research, practice and policy in Finland

Abstract: AimsTo describe pharmacy education, research, practice and policy related to medication adherence in Finland since the year 2000.MethodsThe three universities that provide pharmacy education (Åbo Akademi, University of Eastern Finland, and University of Helsinki) completed a structured pro-forma questionnaire regarding education related to medication adherence. A MEDLINE and EMBASE literature search was performed to identify English language peer-reviewed research that reported medication compliance, adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 59 publications
(138 reference statements)
0
11
0
1
Order By: Relevance
“…An understanding of the role of gender in this respect is also valuable, since gender appears to influence both NA itself and the reasons for NA. The focus of the education and counselling is thus important for the improvement of adherence; it should focus on obstacles to adherence and, according to our study, probably not as much on the cost of the medications as previous studies have shown 59. It is also crucial to distinguish between intentional and unintentional NA when offering individualised counselling 60.…”
Section: Discussionmentioning
confidence: 77%
“…An understanding of the role of gender in this respect is also valuable, since gender appears to influence both NA itself and the reasons for NA. The focus of the education and counselling is thus important for the improvement of adherence; it should focus on obstacles to adherence and, according to our study, probably not as much on the cost of the medications as previous studies have shown 59. It is also crucial to distinguish between intentional and unintentional NA when offering individualised counselling 60.…”
Section: Discussionmentioning
confidence: 77%
“…Adherence research and education have focused on understanding and addressing the contextual factors that contributes to medication non-adherence 27. Demographic characteristics may help to identify patients who are at risk for non-adherence 28.…”
Section: Introductionmentioning
confidence: 99%
“…The results shows that patient counseling is done in all of the hospitals of the Karachi city where survey was conducted, all 30 (100 %) samples provide patient counseling services. Patients should be informed about the need and importance of patient counseling from their perspective and it is very necessary to ensure effective disease management and drug therapy 8 . Pharmacist's involvement in patient care has shown reduced number of hospital admissions and emergency department visits, and improved health status of the patients and their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is erroneous to think that telling patients of side effects will discourage them from using the medication. Holding back information may be disprincipled and patients are authorized to be fully aware of what to look for 8 . Minimum average time consumed for single session of patient counseling was observed as 1.43 minutes while maximum time observed was 6.17 minutes.…”
Section: Discussionmentioning
confidence: 99%